(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
By signing the Bologna Declaration, the Republic of Croatia has committed itself to continuous quality assessment of its higher education system. The paper focuses on the analysis of the scores given by members of the expert panels during the first cycle of re-accreditation of Croatian HEIs for their library resources. The aim of the research was to examine the performance of Croatian academic libraries. The study included all Croatian HEIs which had participated in the re-accreditation process from the very beginning of its implementation (2010/11) until the end of 2015. The total of 129 higher education institutions or parts of institutions were included in the process. The results have shown that Croatian academic libraries received an average score of 3, and that there is no statistically significant difference in the assessment of library resources between university members on one side and polytechnics and colleges on the other, or between public and private HEIs. Furthermore, there is no statistically significant difference between Croatian largest and oldest university centres: Zagreb, Split, Rijeka, and Osijek.